Visualizing the IKEA effect: experiential consumption assessed with fNIRS-based neuroimaging - Oishi, Hiroki; Nakazawa, Kenta; Takahashi, Tomoki; Kyutoku, Yasushi; Dan, Ippeita (Frontiers in Neuroergonomics, 2023)
Introduction In recent years, experiential consumption, which refers to purchases involving hedonic experiences, has been gathering attention in marketing research. Experiential consumption is closely related to cognitive biases, and among them, we focus on the IKEA effect, which is a cognitive bias in which the maximum willingness to pay (WTP) for a product is high because the experience of assembling the product is highly valued. Since no studies have examined the neural mechanism behind the IKEA effect, here we present the first study exploring the neural substrates of the IKEA effect using functional near-infrared spectroscopy (fNIRS). During the WTP evaluation, we expect the attachment to and memory retrieval of DIY products to be the cognitive mechanism for the IKEA effect. Methods Thirty healthy students, of which 24 were confirmed to have undergone the IKEA effect, were asked to perform a WTP evaluation task after assembling three types of do-it-yourself (DIY) products and handling three types of Non-DIY products. Their cerebral hemodynamic responses during the evaluation were measured using fNIRS. In order to adjust for temporal variability of cortical responses among participants, a personalized adaptive general linear model (GLM) analysis was adopted. Then, one-sample t-tests were performed for each DIY and Non-DIY condition for the obtained β values, and a paired t-test was performed between DIY and Non-DIY conditions. Results We identified brain regions, including the left-inferior frontal gyrus (L-IFG) and left-middle frontal gyrus (L-MFG), which were probably related to cognitive processing related to the IKEA effect. Among them, the L-MFG exhibited more activation during the DIY condition than during the Non-DIY condition. Conclusion To our knowledge, the current study is the first to reveal the neural basis of the IKEA effect. The cortical activation during evaluation of WTP for DIY and Non-DIY products exhibited marked differences. In addition to the R-IFG activation often reported for WTP evaluations, we revealed that other regions, in particular the L-IFG and L-MFG, were activated during the DIY condition. These areas are considered to be related to memory and attachment, which would serve as reasonable cognitive constituents for the IKEA effect. In conclusion, this study suggests that the value of experiential consumption can be assessed using fNIRS-based neuroimaging and provides a novel approach to consumer neuroergonomics. It is predicted that visualization the value of experiential consumption will create marketing opportunities for more and more companies and the visualization will become an indispensable method in the future.